THE ROLE OF FOREIGN DEBT, EXPORTS, AND EXCHANGE RATES IN INCREASING INDONESIA'S FOREIGN EXCHANGE RESERVES - Dodi Tirtana; alan miftarova; Fazri Fauzi; Rizky Mohammad Gimnastiar (Business and Economic Analysis Journal, 2025)
Indonesia’s foreign exchange reserves fluctuate due to global and domestic economic dynamics. The problem lies in how key economic factors can maintain the stability and sustainability of national foreign exchange reserves. This study aims to determine the role of foreign debt, exports, and exchange rates in increasing Indonesia’s foreign exchange reserves. This research uses secondary data obtained from the World Bank. The analysis method uses Ordinary Least Squares (OLS) with multiple linear regression. The results show that foreign debt, exports, and exchange rates have a positive effect on Indonesia’s foreign exchange reserves. The implications of this research show that the government needs to strengthen the coordination of fiscal and monetary policies to maintain the stability of foreign exchange reserves. Foreign debt management must be directed toward productive financing that drives exports and economic growth. In addition, a stable and adaptive exchange rate policy is necessary to maintain foreign exchange reserves amid global economic changes.